Eksistensi Nilai-Nilai Pancasila di Era Society 5.0 - Supriatna, Chandra; Bahani, Fadli Nur; Ramzar, Falih Athofa; Hakim, Luqman Muhammad Fadhlul Nul; Kholid, Muhammad Haidar; Dzakwan, Rifqi Muhammad; Furnamasari, Yayang Furi (Indo-MathEdu Intellectuals Journal, 2024)
This article discusses the existence of Pancasila values in the era of Society 5.0. In this era, technology is increasingly dominant and brings new challenges in shaping the nation's character in accordance with the values of Pancasila. This article emphasizes the importance of applying moral and ethical values, especially in balancing digital skills, digital culture, and ethics. Through qualitative methods and literature studies. The method we use is a qualitative method, which is a descriptive method. The main data sources of this research are scientific articles published through google scholar and books relevant to the research topic. Analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusions. The results showed that the values of Pancasila are still relevant and can be applied in the era of Society 5.0, and technology can be used to improve the quality of human life in line with the values of Pancasila.